Activity Strategy Literacy in Increasing Students' Interest in Reading in Elementary Schools (Global Scientific Review, 2023)
Literacy is A term For abilities and skills possessed somebody For understand or understand, process, and use information received For various circumstances. Thereforethat , of course literacy is closely related with life students , both in the environment home , school or public . So that literacy Good used For grow Budi noble character. Research purposes This done For strengthen literacy in increase interest read participant educate . Study implemented at SDN 2 Tilongkabila Bone Bolango Regency. Research carried out is study qualitative with type descriptive with objective For describe with in accordance nature, character something individual, organization or group certain, to make it easy in determine frequency exists connection between something symptom with symptoms in the environment public. Researcher use method descriptive qualitative Because want to see authenticity and existing situation in a way intact , dynamic, meaningful, and complex. Study This No use hypothesis, but study This identify, present , and develop draft regarding school strategy in grow movement literacy school.